Current HRD assays in ovarian cancer: differences, pitfalls, limitations, and novel approaches - Guffanti, Federica; Mengoli, Ilaria; Damia, Giovanna (Frontiers in Oncology, 2024)
Ovarian carcinoma (OC) still represents an insidious and fatal malignancy and few significant results have been obtained in the last two decades to improve patient survival. Novel targeted therapies as PARP inhibitors (PARPi) have been successfully introduced in the clinical management of OC, but not all the patients will benefit and drug resistance almost inevitably occurs. The identification of patients who are likely to respond to PARPi-based therapies relies on homologous recombination deficiency (HRD) tests, as this condition is associated with response to these treatments. This review summarizes the genomic and functional HRD assays currently used in the clinical practice and those under evaluation, the clinical implications of HRD testing in OC and their current pitfalls and limitations. Special emphasis will be placed on the functional HRD assays under development and the use of machine learning and artificial intelligence technologies as novel strategies to overcome the current limitations of HRD tests for a better personalized treatment to improve patient outcomes.